PENGARUH KOMPENSASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT. TAJIRA KARYA PERSADA - Intan Angela Rosariani. S; Arief Syah Safrianto (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
The purpose to determine the effect of compensation and training on employee performance PT. Tajira Karya Persada. This research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires all of whom were employees of PT. Tajira Karya Persada. The research method using partially and simultaneous linear regression analysis. The hypothesis states that both compensation and training have a positive and significant effect on employee performance of PT. Tajira Karya Persada.